E-Learning Mobile Software for Arduino & Its Application (ELA) - Tam, Gin Hsien; Roslan, Hazli (Progress in Engineering Application and Technology, 2022)
In this era of globalization, telecommunications systems that leading towards to the 5G generation have led to E-learning or Electronic-learning that enables students to gain their knowledge through the utilization of electronic equipment or electronic medium. With the utilization of e-learning mobile applications, students can learn and gain knowledge regardless of time and place. However, Arduino users have difficulty finding knowledge about it. They faced problems in the learning process that they do not know what they need to learn about Arduino. Therefore, the project is aimed to develop a mobile application of “ELA” or “E-Learning Arduino & Its Application” that enables and facilitates students in the learning process and enhances knowledge related to Arduino. Android Studio is used in this project to develop “ELA” mobile applications in the form of APK (Android Application Package) or AAB (Android Application Bundle) that are accessible by smartphone and be able to publish to Google Play Store with the utilization of Android app. This app is easy-to-use, and it is completed with information such as the history of Arduino, identification of different Arduino boards & Arduino IDE, and a few examples of electronic projects implemented with Arduino. As a result, ELA was successfully published to the Google Play Store and received 80 ratings with an average rating of 4.875 and 60 reviews from users. “Google forms” had also been used to collect and analyse users’ information, users’ experience with educational mobile applications, and user opinions on ELAs in application evaluation criteria. ELA had successfully solved ELA user problems in Arduino learning. With the usage of Google Form as a user satisfaction questionnaire platform, all information related to the performance of this application is stored and analysed for the purpose of improvement. From the user feedback, it shows that the level of user satisfaction is good and very helpful to those who are new in learning knowledge related to Arduino.